TENDENCIES OF INTERNATIONALIZATION IN RETAILING - Pop Nicolae Alexandru; Dabija Dan Cristian (Annals of the University of Oradea: Economic Science, 2008)
Manufacturing companies took advantage of internationalization as early as in the seventies and eighties of the last century, whereas retail companies have used these chances not before the last few years in order to improve access to resources, to increase sales and to extend activities to external markets. Once a retail company has decided to penetrate a foreign market they must be aware of the unfamiliar working of external environment that they cannot control. Even the world’s leading retailers make mistakes when approaching markets they do not understand properly.